2019
DOI: 10.4103/ijo.ijo_1780_18
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of IL-27 signaling ameliorates herpes stromal keratitis with upregulated CD4+Foxp3+regulatory T cells influx in mice

Abstract: Purpose:The purpose of this study was to investigate the production of IL-27 p28 and EBI3 in the ocular inflammatory sites, and the role of IL-27 signaling in a model of HSV-1 induced herpetic stromal keratitis (HSK).Methods:The BALB/c mice were injected intraperitoneally (24 h before infection) with anti-IL-27 antibody or IgG antibody as control, infected with HSV-1 via corneal scarification, and then injected intraperitoneally with anti-IL-27 antibody or IgG antibody at 1, 3, and 5 days postinfection. Slit l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Moreover, CD4 + CD25 + Tregs can also protect the cornea from more severe lesions, and depletion of CD4 + CD25 + Tregs can accelerate HSK progression (34). A recent study reported that treating the virus-induced inflammatory response with anti-IL-27 antibody can increase the numbers of CD4 + Foxp3 + Tregs, ameliorating tissue damage in the cornea (35). Collectively, Tregs play a protective role in maintaining homeostasis, enhancing immunological tolerance, and preventing autoimmune diseases.…”
Section: The Role Of T Cells In Hskmentioning
confidence: 99%
“…Moreover, CD4 + CD25 + Tregs can also protect the cornea from more severe lesions, and depletion of CD4 + CD25 + Tregs can accelerate HSK progression (34). A recent study reported that treating the virus-induced inflammatory response with anti-IL-27 antibody can increase the numbers of CD4 + Foxp3 + Tregs, ameliorating tissue damage in the cornea (35). Collectively, Tregs play a protective role in maintaining homeostasis, enhancing immunological tolerance, and preventing autoimmune diseases.…”
Section: The Role Of T Cells In Hskmentioning
confidence: 99%
“…HSK, a chronic immunopathological lesion, has been shown to severely impair visual quality (Rajasagi et al, 2017). In particular, over the course of blinding inflammation of the ocular surface, an inadequate immune response increases disease susceptibility, whereas an overreaction induces corneal clouding through inflammatory cell damage; this indicates that balanced immunopathological responses are crucial for preventing corneal clouding, scar formation, and permanent vision loss (Xia et al, 2019). Tregs and the cytokines IL-10 and TGF-β play a protective role by maintaining homeostasis, enhancing immune tolerance, and preventing the onset of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, bilateral disease, recurrent infections, and CS are observed more frequently in immunocompromised patients (Liesegang, 2001). Moreover, a recent study showed that treatment of virus-induced inflammatory responses with anti-IL-27 antibodies increased the number of CD4 + CD25 + Foxp3 + Treg cells and improved corneal tissue damage during relapses (Xia et al, 2019). Overall, previous research has demonstrated that Tregs play a protective role by maintaining homeostasis in vivo, enhancing immune tolerance, improving corneal damage, and preventing the onset of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Indian Journal of Ophthalmology , Xia et al investigate the role of IL-27 signaling in HSV-1 infection using a mouse model of HSK. [4] IL-27 is a heterodimeric cytokine composed of the subunits p28 and EBI3, which bind to the heterodimeric IL-27Rα/gp130 receptor. [4] Although it was initially linked with the development of Th1 responses, it is now recognized as a potent antagonist of different classes of inflammation through its ability to directly modify CD4 + and CD8 + T cell effector functions, to induce IL-10, and to promote specialized T regulatory cell responses.…”
mentioning
confidence: 99%
“…[4] IL-27 is a heterodimeric cytokine composed of the subunits p28 and EBI3, which bind to the heterodimeric IL-27Rα/gp130 receptor. [4] Although it was initially linked with the development of Th1 responses, it is now recognized as a potent antagonist of different classes of inflammation through its ability to directly modify CD4 + and CD8 + T cell effector functions, to induce IL-10, and to promote specialized T regulatory cell responses. Xia et al provide evidence that IL-27 acts as a pathogenic pro-inflammatory cytokine and upregulate CD4 + Foxp3 + Tregs production during the CD4 + T-cell mediated immunity against HSV-1, which ultimately resulted in promoting the progression of HSK and poor prognosis.…”
mentioning
confidence: 99%